MORAL AND AESTHETIC CULTURE AS A COMPLEX SOCIAL PHENOMENON (TAMADDUN NURI JURNALI, 2025)
The article analyzes the issues of moral and aesthetic culture as a complex social phenomenon, the processes and results of moral and aesthetic development of nature at the level of society, moral and aesthetic aspects of work, everyday life and social relations, as well as the specific state of moral and aesthetic views and interests of members of society.